Understanding Delayed T-Cell Priming, Lung Recruitment, and Airway Luminal T-Cell Responses in Host Defense against Pulmonary Tuberculosis - Christopher R. Shaler; Carly Horvath; Rocky Lai; Zhou Xing (Clinical and Developmental Immunology)
Mycobacterium tuberculosis (M.tb), the causative bacterium of pulmonary tuberculosis (TB), is a serious global health concern. Central to M.tb effective immune avoidance is its ability to modulate the early innate inflammatory response and prevent the establishment of adaptive T-cell immunity for nearly three weeks. When compared with other intracellular bacterial lung pathogens, such as Legionella pneumophila, or even closely related mycobacterial species such as M. smegmatis, this delay is astonishing. Customarily, the alveolar macrophage (AM) acts as a sentinel, detecting and alerting surrounding cells to the presence of an invader. However, in the case of M.tb, this may be impaired, thus delaying the recruitment of antigen-presenting cells (APCs) to the lung. Upon uptake by APC populations, M.tb is able to subvert and delay the processing of antigen, MHC class II loading, and the priming of effector T cell populations. This delay ultimately results in the deferred recruitment of effector T cells to not only the lung interstitium but also the airway lumen. Therefore, it is of upmost importance to dissect the mechanisms that contribute to the delayed onset of immune responses following M.tb infection. Such knowledge will help design the most effective vaccination strategies against pulmonary TB.